A Comparative Overview of Current-Use Valuation of Forests for Property-Tax Purposes in the US South. Issue 1 (20th December 2018) - Li, Yanshu
Abstract: Although all southern states provide preferential property-tax incentives to forest landowners, there are great variations in the methodology of forestry-use valuation across the states. This study gives a comparative overview of the methods for current-use valuation of forestry properties across the southern states. Major issues with current practices include inconsistencies in the valuation method and forestry properties under assessment, inconsistencies in measures of incomes and costs, the quality of data for timber growth, insufficient treatment of risks associated with forest management, and the arbitrary limits on capitalization rate. To address these issues, policymakers are advised to ensure the consistency in valuation method and forestry assets, take risks into consideration, weigh the benefits and risks of fixed measures, and introduce adjustment mechanisms to the valuation system.